2021
DOI: 10.1093/mnras/stab3705
|View full text |Cite
|
Sign up to set email alerts
|

The weak dependence of velocity dispersion on disc fractions, mass-to-light ratio, and redshift: implications for galaxy and black hole evolution

Abstract: Velocity dispersion (σ) is a key driver for galaxy structure and evolution. We here present a comprehensive semi-empirical approach to compute σ via detailed Jeans modelling assuming both a constant and scale-dependent mass-to-light ratio M*/L. We compare with a large sample of local galaxies from MaNGA and find that both models can reproduce the Faber-Jackson (FJ) relation and the weak dependence of σ on bulge-to-total ratio B/T (for B/T ≳ 0.25). The dynamical-to-stellar mass ratio within R ≲ Re can be fully … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…Bluck et al (2019Bluck et al ( , 2022 showed that central stellar velocity dispersion is the main galactic property linked to the level of sSFR, in the local universe. Marsden et al (2022) also showed that at fixed stellar mass, the stellar velocity dispersion remains constant for B/T>0.2. These recent results are in line with our findings pointing to a significant role of the bulges in the quenching process.…”
Section: Causes and Consequences Of The Presence Of The Bulgementioning
confidence: 80%
“…Bluck et al (2019Bluck et al ( , 2022 showed that central stellar velocity dispersion is the main galactic property linked to the level of sSFR, in the local universe. Marsden et al (2022) also showed that at fixed stellar mass, the stellar velocity dispersion remains constant for B/T>0.2. These recent results are in line with our findings pointing to a significant role of the bulges in the quenching process.…”
Section: Causes and Consequences Of The Presence Of The Bulgementioning
confidence: 80%
“…Ho we ver, Ho et al ( 2009 ) measured σ using the spectra of the central regions of the galaxies typically dominated by the bulge. Furthermore, Marsden et al ( 2022 ) reported weak dependence of σ on disc component. On the other hand, we find ALGs do not deviate from the best-fitting inactive L R, core − σ relation defined by the H II + ALG subsample, but they reside almost exclusively under this relation.…”
Section: R Core − M Bh and L R Core − σmentioning
confidence: 99%
“…of luminous as well as dark galactic matter -if learnt or estimated, will permit computation of the spatial distribution of dark matter in the galaxy. Ubiquity of the shape of the total gravitational mass density function continues to be questioned [1][2][3] , while agreement exists on the importance of galactic mass distribution in constraining galaxy formation [1,[4][5][6] , and evolution [7,8] . Computation of the spatial distribution of dark matter in a galaxy, will indeed need to include astronomical models of the link between luminous galactic matter, and photometric information obtained from such matter in the galaxy.…”
Section: Introductionmentioning
confidence: 99%